DEVELOPMENT OF PODCAST-BASED TEACHING MATERIALS FOR STUDENTS OF THE ISLAMIC COMMUNICATION AND BROADCASTING STUDY PROGRAM AT IAIN METRO - indah librianti, eka octalia (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
This study aims to develop podcast-based teaching materials as an innovative digital learning media for students of the Islamic Communication and Broadcasting Study Program (KPI) at IAIN Metro. The background of this study is based on the low utilization of interactive digital media in the learning process and the absence of the use of podcasts as a means of two-way communication between lecturers and students. The research method used is Research and Development (R&D) with a development model that includes the planning stage, product design, design validation, product revision, field trials, as well as dissemination and implementation. The product developed is educational podcast content resulting from a collaboration between Shawtuna FM Radio and the Spotify application, with learning themes from several courses such as Introduction to Communication Science, Political Communication, Journalistic Photography, and Master of Ceremony. The validation results showed a very high level of feasibility, with a percentage of assessments from material experts of 86.6% and media experts of 89.8%. Field trials on 37 students resulted in an average feasibility of 87.7% with the category of